Business Plan : Medin Fragrance / Nur Amirah Makhtar … [et al.] - Makhtar, Nur Amirah; Azmi, Nur Nadia; Che Ujang, Nur Asmazeera; Nawi, Nur Farah Izzati; Mohd Sabri, Nurul Ain Nabila (2021)
Medin Fragrance provides consumers with fragrance products and services, offering a range of varieties of perfume with a distinctive style bottle and exclusive packaging that provides high customer satisfaction. My customers recognise every class of community, especially adults who want to use a long-lasting fragrance product at an affordable price without much difficulties. I also target the person who is busy with their job but still wants the best fragrance for their everyday use such as office employees, lecturers and students, because I know they were busy with their job so that they don't have time to buy perfume on the market. So, I find website-building alternatives to buying through online purchasing. In addition, Medin Fragrance offers a long last fragrance that provides relieve during the day, wudhuk pleasant, healthy for all ages to use. Over the course of the year the Medin Fragrance company has seen rapid growth across Kuala Lumpur. Kuala Lumpur is a busy city with lots of buildings and people living and working there. This allows the market for perfume to increase during the year. Although there are currently might have business out there like me, but I have my own specific products and my customer special services as well. The marketing strategy for Medin Fragrance is to underline the quality and price of my products. The cheap and fair price I give is because not everyone in Kuala Lumpur is affluent or comes from the social culture of the upper class. I am assured, however, that everyone can afford to buy my stuff. I therefore create marketing strategies that encourage people who like fragrance products to come to my premises in particular. Medin Fragrance's management consists of five senior employees, Nur Asmazeera as chief executive manager, Nur Amirah as operation manager, Nurul Ain Nabila as administrator (Social Media), Nur Nadia as marketing and Nur Farah Izzati as financial manager. My staff have a lot of company experience. I already have the product engagement strategy to establish my brand efficiently by changing the medium, including signboard, radio, and others. I already have the product and services commitment plan to aggressively build my brand through variation of medium including signboard, radio, and others.